A contribution to the empirics of food price behavior: the case of rice price dynamics in Italy. Issue 1 (3rd September 2020) - Barboza, Gustavo; Gavinelli, Laura; Pede, Valerien; Mazzucchelli, Alice; Di Gregorio, Angelo
Abstract : Purpose: The purpose is to detect the nonlinearity wholesale rice price formation process in Italy in the 1995–2017 period. Design/methodology/approach: A nonlinear smooth transition autoregressive (STAR)-type dynamics model is used. Findings: Wholesale rice prices are significantly affected by variations in the international price of rice as well as variations in Arborio price. Research limitations/implications: The limitations include policy recommendations for the production and commercialization of rice in Italy. Practical implications: Understanding rice pricing dynamics and nonlinearity behavior is pivotal for the survival of the entire European and Italian rice supply chain. Originality/value: In the extant literature, no evidence exists on non-linearity of rice prices in Italy.